Cartel Duration and Endogenous Private Monitoring and Communication: An Instrumental Variables Approach - Jun Zhou (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2012)
Colluding firms often exchange private information and make transfers within the cartels based on the information. Estimating the impact of such collusive practices' known as the 'lysine strategy profile (LSP)' on cartel duration is difficult because of endogeneity and omitted variable bias. I use firms' linguistic differences as an instrumental variable for the LSP in 135 cartels discovered by the European Commission since 1980. The incidence of the LSP is not significantly related to cartel duration. After correction for selectivity in the decision to use the LSP, statistical tests are consistent with a theoretic prediction that the LSP increases cartel duration.
urn:nbn:de:bvb:19-epub-13185-6
Keywords: D43; K21; K42; L13; 330; the lysine strategy profile; post-agreement information exchange; within-cartel transfers; monitoring; verification and promotion of compliance; cartel duration; endogenous covariates; Kartell; Dauer; Nachhaltigkeit; Informationsverbreitung; Theorie; Schätzung; EU-Staaten